Wind resistance aerial path planning for efficient reconstruction of offshore ship. Issue 1 (31st December 2022) - Liu, Tao; Shen, Ruiqi; Lei, Zhengling; Huo, Yuchi; Zhao, Jiansen; Xu, Xiaogang
ABSTRACT: When the unmanned aerial vehicle (UAV) is applied to three-dimensional (3D) reconstruction of the offshore ship, it faces two problems: the battery capacity limitation of the UAV and the disturbance of the wind in the environment. Wind disturbance is generally not considered in the path planning process of the existing UAV 3D reconstruction path planning research. Therefore, the planned path is only suitable for no-wind or light-wind scenarios. For the 3D reconstruction of ship targets, we propose a UAV path planning method that can satisfy both reconstruction efficiency and wind disturbance resistance requirements. Firstly, the concept of model surface complexity is proposed to generate a more efficient candidate view set. Secondly, the Min–Max strategy and a new viewpoint construction method are used to generate the initial path. Thirdly, combined with the wind field model, a method for generating a stable path against wind disturbance based on the idea of interval optimization is proposed. Experimental results demonstrate that our method can adaptively determine the number of sample points and viewpoints according to ship's geometric characteristics and further reduce the number of viewpoints without significantly affecting the reconstruction quality; the path planned by our method is also stable against wind disturbance.